Reactive polymer blending - Baker, W. E. (Hanser Publishers ; Hanser Gardner Publications, 2001)
Much enabling technology is required to produce commercially viable blends including compatibilization chemistry, blend rheology, process equipment and morphology control. This volume is particularly suitable for students as a graduate level textbook and for practitioners trying to optimize these products and processes.
Keywords: Polymers.; Plastics.; elektronické knihy; electronic books